Polemics on the Ways of Development of Russian Literature in Russian Critical Literature Abroad in the 1920–1930s - Anna V. Protopopova; Ivan A. Protopopov (Studia Litterarum)
The paper is devoted to the polemics on the ways of development of Russian literature in emigration, in which Mark Slonim, Zinaida Gippius, Alfred Bem, Vladislav Khodasevich, and Georgii Adamovich all took part. The article considers the critical views of Khodasevich and Adamovich in relation to the position of Slonim, whose article “Living Literature and Dead Critics” made these polemics central to the emigrant critical literature of the 1920–1930s. Slonim thought that emigrant literature was only a branch of the common trunk of Russian literature that remained in Soviet Russia. According to Khodasevich, any literary tradition representing Russian literature in emigration never developed, and the array of different works of individual authors could not form the unity called emigrant literature. Adamovich, even though he denied the possible development of Russian literature, believed that the problem could be solved by the artistic expression of an individual’s self in simple forms of language devoid of any beauty.